Efficiency of combined Fe and Pb radiation shield of transport casks for SNF transportation - Rudychev, V.G.; Azarenkov, M.O.; Girka, I.O.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2022)
The possibility of increasing the efficiency of combined iron and lead shielding of transport containers (TC) for SNF transportation by railroad is studied. Models for the transport of SNF γ-quanta are developed, that make it possible to determine the dose rates behind thick shields using the Monte Carlo method. It is shown that for layers of the same mass thickness: the layer of Fe with the thickness of 15 cm, and the layer of Pb with the thickness of 10.4 cm which is equivalent to 15 cm of iron, placement of Fe in the first layer, and Pb in the second layer provides increase of attenuation of the gamma flux by more than 2 times as compared with the reverse order. The attenuation of SNF neutrons by Fe and Pb shields is studied. The gamma flux from SNF can be decreased by ∼ 1.5 times by placement of the most of Fe to the first layer without changing the weight of both layers, in the HI-STAR190UA TC. Досліджено можливість підвищення ефективності комбінованих захистів з Fe та Pb транспортних контейнерів (ТК) для перевезення ВЯП залізницею. Розроблено моделі транспорту γ-квантів ВЯП, що дозволяють визначити методом Монте-Карло потужності доз за захистами великої товщини. Показано, що для шарів однакової масової товщини: Fe = 15 см, Pb = 10.4 см еквівалентним 15 см заліза, розміщення в першому шарі Fe, а у другому – Pb послаблює потік квантів більш ніж удвічі. Досліджено ослаблення нейтронів ВЯП захистами з Fe та Pb. При перенесенні більшої частини заліза в перший шар без зміни ваги як Fe, так і Pb, в ТК HI-STAR190UA потік квантів ВЯП зменшується в ∼ 1,5 рази.